Effect of Jatropha Curcas Plant on Some Soil Quality in Part of the Semi-Arid Zone of Nigeria - Yusuf, Ladan; Mohammed, Ahmed; Abdul, Mohammed Mansur; Ahmed, Adamu (FUDMA Journal of Sciences, 2026)
The global land productivity is continuously decline due to land degradation and subsequently reduce the soil quality. The research aimed at assessing the effects of Jatropha Curcas plant on some soil quality and evaluate the erodibility status of the area. The Jatropha plantation land was demarcated and adjacent to it cultivated land were used as sampling location. Ten soils samples were randomly collected in each of the sampling location using composite sampling techniques from 0 – 15 cm depth. The laboratory results were analysed using descriptive also student’s t-test was used at 0.05 probability level. The results revealed that mean values of organic carbon (0.94%), organic matter (1.87%), Infiltration rate (12.56mm), %clay (8.8%), %silt (9.6% ), soil carbon stock (2464.5ton) were all found higher at Jatropha site than control site. This implies that jatropha have the capacity to enhance and retain some soil quality parameters. It was discovered that cultivated land is more susceptibility to erosion due to high erodibility status (24.54ton/ha) than the Jatropha site (23.29ton/ha). This signified that jatropha plantation improve soil quality and reduce soil vulnerability to erosion. This is further, testified by t-test whereby significant difference in the mean values of organic matter, organic carbon, infiltration rate, soil carbon stock, soil erodibility was observed. It was concluded that Jatropha curcas have the ability improve soil quality parameter and therefore, reduce land degradation.